FORMATION OF BUSINESS SUSTAINABILITY OF THE TRANSPORT INDUSTRY IN THE CONTEXT OF INNOVATIVE TRANSFORMATIONS - Zarina POBEREZHNA (Scientific Journal of Silesian University of Technology. Series Transport)
The paper describes the peculiarities of the formation of business sustainability in the transport industry, and characterizes the main factors affecting it. It was determined that for the business sustainability of the transport industry, innovative processes and transformations play a significant role, which encourage enterprises to be client-oriented and provide quality service to consumers, the ability to adapt to changes in the economic situation and new social challenges. A feature of the modern development of the transport industry is the transition to an innovative path of development, which will allow transport enterprises to occupy more priority positions compared to their competitors. The impact of innovative transformations on ensuring business sustainability of the transport industry is characterized by the use of innovations in the implementation of commercial activities, ensuring the quality of services (products), which will make it competitive. The paper offers a methodical approach to choosing a strategy for managing the business sustainability of the transport industry in the conditions of innovative transformations, which allows choosing an appropriate development strategy depending on the indicators of economic activity (IEA), the level of business sustainability (IBS), risk indicators (IBR).